2013
DOI: 10.1051/0004-6361/201322167
|View full text |Cite
|
Sign up to set email alerts
|

On central black holes in ultra-compact dwarf galaxies

Abstract: Context. The dynamical mass-to-light (M/L) ratios of massive ultra-compact dwarf galaxies (UCDs) are about 50% higher than predicted by stellar population models. Aims. Here we investigate the possibility that these apparently elevated M/L ratios of UCDs are caused by a central black hole (BH) that heats up the internal motion of stars. We focus on a sample of ∼50 extragalactic UCDs from the literature for which velocity dispersions and structural parameters have been measured. Methods. To be self-consistent i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
201
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(227 citation statements)
references
References 92 publications
(234 reference statements)
23
201
3
Order By: Relevance
“…For VUCD3, we found that with a BH mass of M 4.4 10 6  , Γ with three-sigma error bars was 0.8±0.6 resulting in a total dynamical mass of 32  M 21 10 6  . For comparison, without a BH component Γ with 3σ error bars was 1.7±0.2 resulting in a total dynamical mass of M 66 8 10 6 ´, which is consistent with previous results (Evstigneeva et al 2007;Mieske et al 2013). For M59cO, we found that, with a BH mass of M 5.8 10 6  , Γ with 3σerror bars was 0.3±0.2, resulting in a total dynamical mass of M 32 10 22 24 6 -+  .…”
Section: Isotropic Model Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For VUCD3, we found that with a BH mass of M 4.4 10 6  , Γ with three-sigma error bars was 0.8±0.6 resulting in a total dynamical mass of 32  M 21 10 6  . For comparison, without a BH component Γ with 3σ error bars was 1.7±0.2 resulting in a total dynamical mass of M 66 8 10 6 ´, which is consistent with previous results (Evstigneeva et al 2007;Mieske et al 2013). For M59cO, we found that, with a BH mass of M 5.8 10 6  , Γ with 3σerror bars was 0.3±0.2, resulting in a total dynamical mass of M 32 10 22 24 6 -+  .…”
Section: Isotropic Model Resultssupporting
confidence: 90%
“…Recently, analyses of the integrated dispersions of UCDs revealed an interesting property; the dynamical mass appears to be elevated by∼50% for almost all UCDs above M 10 7  when compared to the mass attributed to stars alone (e.g., Haşegan et al 2005;Mieske et al 2013). These dynamical mass estimates have been made combining structural information from Hubble Space Telescope (HST) imaging with groundbased, global velocity dispersion measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least some UCDs contain a central supermassive black hole (see Seth et al 2014;Janz et al 2015 for detections, andFrank et al 2011;Norris et al 2015 for non-detections). UCDs appear not to have high dark matter fractions (Frank et al 2011;Mieske et al 2013;Forbes et al 2014;Janz et al 2015).…”
Section: Introductionmentioning
confidence: 91%
“…As shown above, the variable IMF (scenario (1)) can explain the observed elevated M/L V values. The mass of a SMBH in scenario (2) required to explain the observed M/L V values, needs typically to be 10-15 per cent of the present-day UCD mass (Mieske et al 2013). The presence of SMBHs with such masses is indeed suggested or observationally confirmed at least for a few UCDs (e.g.…”
Section: The Implications Of Observed M/l V -Ratiosmentioning
confidence: 99%